Neural correlates of prospective memory in college students with anxiety - Rice, Michaela; Hansen, Melissa; Thomas, Michael L.; Davalos, Deana (Frontiers in Psychology, 2024)
Introduction Prospective memory (PM) is the ability to create and execute future tasks. It is comprised of two components: cue detection and intention retrieval. PM is essential for performing high-level goals, a proficiency extremely important in college populations. Anxiety is a prevalent psychological experience in college populations that may be associated with impairments in PM. The present study examined PM performance and anxiety in college students, using neurophysiology to measure the mechanism of impairment. Methods After self-reporting anxiety levels, 80 participants completed an event-based, focal PM task while two event-related potentials were recorded from an electroencephalogram: the N300 to assess cue detection, and the prospective positivity to assess intention retrieval. Results The results demonstrated that, when controlling for age and gender, higher state anxiety was significantly associated with lower PM accuracy (β = −0.27, p = 0.020) and lower prospective positivity amplitude (β = −0.04, p = 0.021). Lower prospective positivity amplitude was significantly associated with lower PM accuracy (β = 0.27, p = 0.015). Higher state anxiety was significantly indirectly associated with lower PM accuracy mediated by lower prospective positivity amplitude (ab = −0.11, p = 0.047). Discussion These findings suggest intention retrieval could be a key component in supporting PM for college students with high state anxiety.